1997
DOI: 10.1111/j.1365-2702.1997.tb00303.x
|View full text |Cite
|
Sign up to set email alerts
|

A conceptual framework for advanced practice: an action research project operationalizing an advanced practitioner/consultant nurse role

Abstract: A preliminary conceptual framework for an advanced practice/consultant nurse role is presented which links the role to its context and outcomes. The conceptual framework was developed in the process of analysing data from a 3-year action research study involving the operationalization of an advanced practice/consultant nurse role in a Nursing Development Unit. The skills and knowledge base of consultancy, underpinned by a strong nursing foundation, augmented by strong leadership and combined with the educator … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
145
1
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 184 publications
(155 citation statements)
references
References 14 publications
7
145
1
2
Order By: Relevance
“…These concepts were in accordance with the concepts related to the study of Douglas et al (2004) and Manley (1997) as well as Gaboury et al (2010) that assessed the collaboration in the form of system input.…”
Section: Discussionmentioning
confidence: 65%
See 4 more Smart Citations
“…These concepts were in accordance with the concepts related to the study of Douglas et al (2004) and Manley (1997) as well as Gaboury et al (2010) that assessed the collaboration in the form of system input.…”
Section: Discussionmentioning
confidence: 65%
“…In another study, one of the concepts of showed model was care continuity [27]. In the study by Manley (1997) the final outcome of collaboration framework was the quality of services provided to patients [26]. In this study, the process emerged in the form of 9 themes.…”
Section: Outcomes Of Collaborationmentioning
confidence: 93%
See 3 more Smart Citations